Potential biomarkers for the early detection of acute kidney injury after percutaneous nephrolithotripsy. (2nd January 2016) - Daggülli, Mansur; Utangaç, Mehmet M.; Dede, Onur; Bodakci, Mehmet N.; Hatipoglu, Namık K.; Penbegül, Necmettin; Sancaktutar, Ahmet A.; Bozkurt, Yaşar; Söylemez, Haluk
Abstract: This study aims to investigate the role of urinary biomarkers in the determination of the potential risks of renal parenchymal tubular damage in adult patients who underwent percutaneous nephrolithotomy (PNL) with the indication of renal stone. A randomized and prospective controlled study was performed between June and December 2013. We enrolled 29 consecutive patients with renal calculi > 2 cm and who underwent PNL, as well as 47 healthy control subjects. Urine samples, including 2 h before surgery, 2 and 24 h after surgery were collected from the patient group. Freshly voided urine samples were collected from the control group. Kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), N-acetyl-glucosaminidase (NAG), and liver-type fatty acid binding protein (LFABP) levels were measured from these urine samples. The mean KIM-1/Cr value that measured 24 h after the operation was statistically significant, higher than its preoperative (preop) level ( p = 0.045). A significant difference was detected between the mean preop and postoperative (postop) 24 h NAG/Cr values ( p < 0.001). Also, postop 24 h NGAL/Cr levels were statistically significant, higher than its preop levels ( p = 0.013). According to the comparison of preop and postop levels, an increase in LFABP/Cr values secondary to surgical intervention was observed without any statistically significant difference. Besides the LFABP/Cr levels do not change after percutaneous kidney surgery, KIM-1/Cr, NAG/Cr, and NGAL/Cr levels increase postop period, especially at 24 h. Further studies with a larger series and repeated measurements should be performed to clarify if they can be used to demonstrate renal damage after percutaneous surgery or not.